Gênero e educação superior: perspectivas de alunas de física - Amorim, Valquiria Gila de (2017)
Physics is a predominantly male field, and the reasons for this absence of women in the field are not sufficiently recognized or investigated, especially in Brazil. This dissertation aimed to analyze the experiences of inclusion and exclusion undergone by female students acquiring an undergraduate degree in Physics at Federal University of Paraíba (UFPB), Brazil. The theoretical approach was based on feminist and gender studies and cultural studies of science, which are interdisciplinary. The methodological approach was qualitative and two strategies of data collection were used in order to analyze the influence of family members and teachers in the choice of Physics, and their formative trajectory at the university: face-to-face and online structured interviews. However, male students’ perspectives were included to analyze the context of gender relations in the field of Physics, and how these relations may disadvantage women in contrast to men. Women's testimonies revealed embarrassing, debilitating and challenging experiences, as well as gender barriers, such as the chilly climate from the beginning, the male image of the Physicist, the lack of credibility of women in the field, and sexism and sexual harassment from male colleagues and professors. In conclusion, the data indicated that in order to remain in the Physics field, female students face gender stereotypes, prejudices, discrimination, sexism and sexual harassment, which remained invisible and naturalized in many situations.